Complete genome sequencing of Dehalococcoides sp. strain UCH007 using a differential reads picking method. Issue 1 (December 2015) - Uchino, Yoshihito; Miura, Takamasa; Hosoyama, Akira; Ohji, Shoko; Yamazoe, Atsushi; Ito, Masako; Takahata, Yoh; Suzuki, Ken-ichiro; Fujita, Nobuyuki
Abstract A novelDehalococcoides sp. strain UCH007 was isolated from the groundwater polluted with chlorinated ethenes in Japan. This strain is capable of dechlorinating trichloroethene, cis -1, 2-dichloroethene and vinyl chloride to ethene.Dehalococcoides bacteria are hardly cultivable, so genome sequencing has presented a challenge. In this study, we developed a differential reads picking method for mixed genomic DNA obtained from a co-culture, and applied it to the sequencing of strain UCH007. The genome of strain UCH007 consists of a 1, 473, 548-bp chromosome that encodes 1509 coding sequences including 29 putative reductive dehalogenase genes. Strain UCH007 is the first strain in the Victoria subgroup found to possess thepceA, tceA andvcrA genes.